2010
DOI: 10.1111/j.1538-7836.2009.03662.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved high molecular weight kininogen inhibits tube formation of endothelial progenitor cells via suppression of matrix metalloproteinase 2

Abstract: Background and objective Endothelial progenitor cells (EPCs) contribute to postnatal neovascularization, thus promoting wide interest in their therapeutic potential in vascular injury and prevention of their dysfunction in cardiovascular diseases. Cleaved high molecular weight kininogen (HKa), an activation product of the plasma kallikrein-kinin system (KKS), inhibits the functions of differentiated endothelial cells including in vitro and in vivo angiogenesis. In this study, our results provided the first evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Downregulation of MMP2 was also observed in the transfectants by zymography and Q-PCR. The stimulation of MMP2 by VEGF has been reported in endothelial progenitor cells; knockdown of MMP2 by small interfering RNA and suppression of MMP2 by kininogen inhibits tube formation of endothelial progenitor cells in vitro (Wu et al, 2010). Downregulation of MMP2, which contributes to the angiogenesis inhibition of the FBLN2S stable transfectants, may be associated with the reduced expression of VEGF.…”
Section: Tumor-suppressor Gene Fbln2 Ewl Law Et Almentioning
confidence: 92%
“…Downregulation of MMP2 was also observed in the transfectants by zymography and Q-PCR. The stimulation of MMP2 by VEGF has been reported in endothelial progenitor cells; knockdown of MMP2 by small interfering RNA and suppression of MMP2 by kininogen inhibits tube formation of endothelial progenitor cells in vitro (Wu et al, 2010). Downregulation of MMP2, which contributes to the angiogenesis inhibition of the FBLN2S stable transfectants, may be associated with the reduced expression of VEGF.…”
Section: Tumor-suppressor Gene Fbln2 Ewl Law Et Almentioning
confidence: 92%
“…MMP-2 and MMP-9 participate in the mobilization of EPCs. Recently we have demonstrated that MMP-2 is selectively required for VEGF-stimulated vasculogenic differentiation of EPCs [11]. In the conditioned culture media of EPCs embedded in 3D collagen gel, VEGF selectively stimulated the secretion and activation of MMP-2, but not MMP-9, and VEGF-stimulated proMMP-2 expression and secretion are time-dependent, the secreted proMMP-2 was meanwhile converted into active form.…”
Section: Hka Inhibits Epc Tube Formation Via Suppression Of Mmp-2 Actmentioning
confidence: 99%
“…In the conditioned culture media of EPCs embedded in 3D collagen gel, VEGF selectively stimulated the secretion and activation of MMP-2, but not MMP-9, and VEGF-stimulated proMMP-2 expression and secretion are time-dependent, the secreted proMMP-2 was meanwhile converted into active form. As the specific inhibitor of MMP-2 (444244), but not MMP-9 (444278), concentration-dependently attenuated VEGFstimulated tube formation by EPCs, suggesting the role of MMP-2 activities in tube formation by EPCs [11]. The requirement of MMP-2 and MMP-9 expression for the tube formation by EPCs is examined by specific siRNA oligonucleotides.…”
Section: Hka Inhibits Epc Tube Formation Via Suppression Of Mmp-2 Actmentioning
confidence: 99%
See 2 more Smart Citations